Effect of CAPN1 gene polymorphism on some physical and sensory traits in broiler meat - Ali Ahmed Abdul-Kareem; Abdul-Kadhum Dakhil Raysan (University of Thi-Qar Journal of agricultural research, 2022)
This study was conducted in the poultry field, Animal Production Department, College of Agriculture and Marshes, University of Thi-Qar, from 10/11/2021 to 3/2/2022, the period included field and laboratory stud. A total of 100, one day broilers Ross 308 were used. Laboratory analyzes were carried out in the laboratories of the Marshes Research Center, University of Thi-Qar and the laboratories of the College of Agriculture and Marshes, University of Thi-Qar. Three genotypes CC, CT and TT were identified whose frequency was 0.52, 0.34 and 0.14 respectively and the frequency of the C allele was 0.69 and the frequency of the T allele was 0.31. There were significant differences on Water Holding Capacity (WHC) among the genotypes, the CC genotype was superior to the CT and TT genotypes. As for the thawing and cooking loss, there were no significant differences between the genotypes. A significant differences on pH values among the genotypes, the CC genotype was superior to the CT and TT genotypes. Significant differences in flavor between genotypes, the CC genotype was superior to the CT genotype, and the CT genotype was superior to the TT genotype. Highly significant differences in tenderness, the CC genotype was superior to the TT genotype, while the CT genotype did not differ significantly from the CC and TT genotypes. Highly significant differences between the genotypes in juiciness, the CC genotype was superior to the CT and TT genotypes. No significant differences in color and general acceptable.